USM: THE CHOICE OF 17 INDONESIAN STUDENTS - MPRC, Pusat Media & Perhubungan Awam (USM, 2016)
USM, PENANG, 17 March 2016 – Universiti Sains Malaysia (USM) has long been the choice of students from Indonesia to pursue their studies further. Currently there are close to 200 students from Indonesia who are doing their studies here at the undergraduate as well as the postgraduate level.